Synthesis and biological evaluation of thiazole derivatives as novel USP7 inhibitors. Issue 4 (15th February 2017) - Chen, Chao; Song, Jiemei; Wang, Jinzheng; Xu, Chang; Chen, Caiping; Gu, Wei; Sun, Hongbin; Wen, Xiaoan
Graphical abstract: Abstract: Herpesvirus-associated Ubiquitin-Specific Protease (HAUSP, also called USP7) interacts with and stabilizes Mdm2, and represents one of the first examples that deubiquitinases oncogenic proteins. USP7 has been regarded as a potential drug target for cancer therapy. Inhibitors of USP7 have been recently shown to suppress tumor cell growth in vitro and in vivo. Based on leading USP7 inhibitors P5091 and P22077, we designed and synthesized a series of thiazole derivatives. The results of in vitro assays showed that the thiazole compounds exhibited low micromolar inhibition activity against both USP7 enzyme and cancer cell lines. The compounds induced cell death in a p53-dependent and p53-independent manner. Taken together, this study may provide thiazole compounds as a new class of USP7 inhibitors.